Essays in conveyancing and property law in honour of Professor Robert Rennie - Bogle, Stephen; Chalmers, James, 1976-; McCarthy, Frankie; Rennie, Robert, 1947-; Open Book Publishers (Open Book Publishers, 2015)
"Professor Robert Rennie has been one of the most influential voices in Scots private law over the past thirty years. Highly respected as both an academic and a practitioner, his contribution to the development of property law and practice has been substantial and unique. This volume celebrates his retirement from the Chair of Conveyancing at the University of Glasgow in 2014 with a selection of essays written by his peers and colleagues from the judiciary, academia and legal practice. Each chapter covers a topic of particular interest to Professor Rennie during his career, from the historical development of property law rules through to the latest developments in conveyancing practice and the evolution of the rules of professional negligence. Although primarily Scottish in focus, the contributions will have much of interest to lawyers in any jurisdiction struggling with similar practical problems, particularly those with similar legal roots including the Netherlands and South Africa. As a whole, the collection is highly recommended to students, practitioners and academics."--Publisher's website.
Contributors -- Preface -- 1. Robert Rennie: A Career Retrospective / Lord Bonomy -- ACQUIRING PROPERTY -- 2. "Tell Me, Don't Show Me" and the Fall and Rise of the Conveyancer / Professor Kenneth G C Reid -- 3. A Puzzling Case about Possession / Lord Hope of Craighead -- 4. "It's in the Post": Distance Contracting in Scotland 1681-1855 / Professor Hector L MacQueen -- 5. Assignation of All Sums Securities Dr Ross Anderson -- DEFECTS IN ACQUISITION AND HOW TO FIX THEM -- 6. Property Law, Fiduciary Obligations and the Constructive Trust / Lord Hodge -- 7. The Offside Goals Rule and Fraud on Creditors / Dr John MacLeod -- 8. A New Era in Conveyancing: Advance Notices and the Land Registration etc. (Scotland) Act 2012 / Ann Stewart -- 9. Bona Fide Acquisition: New in Scottish Land Law? / Professor David Carey Miller --ENJOYING PROPERTY -- 10. Res merae facultatis: Through a Glass Darkly / Sheriff Douglas J Cusine -- 11. The Use of Praedial Servitudes to Benefit Land outside the Dominant Tenement / Professor Roderick R M Paisley -- 12. Enforcing Repairing Obligations by Specific Implement Professor / Angus McAllister -- 13. Two Questions in the Law of Leases / Lord Gill --THE FUTURE OF PROPERTY LAW -- 14. Conveyancing: A Bright Digital Future? / Professor Stewart Brymer -- 15. Islamic Mortgages and Scots Law / Professor George Gretton -- 16. Completion of the Land Register: The Scottish Approach / John King -- PROFESSIONAL NEGLIGENCE IN PRINCIPLE AND PRACTICE -- 17. Primary Clients, Secondary Clients, Surrogate Clients and Non-clients: The Expanding Duty of Care of Scottish Solicitors / Kenneth Swinton -- 18. The Court and the Conveyancing Expert / Lady Paton -- 19. The Role of the Expert Witness in Professional Negligence Litigation / Gerald F Hanretty QC -- 20. Robert Rennie: A Bibliography / Bernadette O'Neill -- Index.
Available through Open Book Publishers.
"Robert Rennie : a bibliography": pages 395-401.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Keywords: Rennie, Robert, -- 1947-; Conveyancing -- Scotland; Negligence -- Scotland; Real property -- Scotland